The Institutionalisation of Corporate Social Responsibility (CSR). A Case Study of British Grocery Retailing - Hempsall, AM (2015)
This case study investigates the institutionalisation of corporate social responsibility (CSR) in the grocery retail industry. The research uses the lens of institutional theory to understand the macro-institutional pressures that influence firms to engage in CSR and how the powerful actors involved, influence their meso and micro institutional environments. Early neo-institutional theories argue that when disparate organisations are structured into a specific field, powerful forces emerge that shape the institutional environment and make them more similar to one another, or ‘isomorphism’.